United States : Selected Issues. (IMF Staff Country Reports; Country Report, 2004)
This Selected Issues paper examines the role of information and communication technology (ICT) in the recent acceleration of labor productivity growth in the United States. The analysis reveals that the increase of total factor productivity (TFP) growth is a broad phenomenon that encompasses non-ICT producing sectors, consistent with the view that ICT is a 'general purpose technology.' The paper investigates whether the productivity boom may have dampened employment in recent years. It also assesses the contribution of immigrants to the United State economy.